English book series for elementary school students : Rainbow 4 / Christina Kristiyani, Kristina Yuliarti ; editor, Flora Maharani, Indah Sri Utami - CHRISTINA KRISTIYANI; Yasintha Dyah Pertiwi; Flora Maharani; Indah Sri Utami (Kanisius, 2014)
xii, 113 hlm. : ilus. ; 25 cm.